Pengembangan UMKM di Kabupaten Tuban - Hariyoko, Yusuf (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Implementation of SME's development in Tuban District. The development of SME's becomes an responsibilty for every region, because of this sector is able to absorb a lot of labor and also have positive developments in economic development efforts in the region. The theory used are economic development and SME's. The results of this study are 1) Local government commitment in the development of MSMEs is still not optimal and can be improved further by strengthening the various sectors supporting the development of SME's. 2) In the development of SME's in Tuban Regency is the responsibility of several parties, but there are still some parties whose role and business is still not optimal. 3) The types of activities that have been carried out varied and attempted responsively may be undertaken by local governments, but there are still some important records that need to be improved. It aims to improve the quality of the people's economy from the macro and micro sectors Keywords: SME's, Economic Development